2017
DOI: 10.1016/j.euf.2016.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Recurrent Somatic Mutations with Clinical Outcomes: A Pooled Analysis of 1049 Patients with Clear Cell Renal Cell Carcinoma

Abstract: Background Analyses of associations between clinicopathologic outcomes and recurrent somatic mutations in clear cell renal cell carcinoma (ccRCC) have been limited to individual cohorts. Objective To define clinicopathologic associations between specific mutations and ccRCC disease characteristics. Design, setting, and participants DNA sequencing data were pooled from three collaborative genomic cohorts (n = 754) and our institutional database (n = 295). All patients had clinical data and identification of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 25 publications
0
29
0
Order By: Relevance
“…As inactivation of VHL is the founding event of ccRCC, its mutation status has no effect on clinical outcome, whereas mutations involved in disease progression such as PBRM1 , SETD2 and BAP1 as well as KDM5C (which is also involved in chromatin modification) were shown to associate with aggressive clinical features 7779 . Small renal masses harbouring PBRM1 mutations were associated with stage III pathological features (that is, extrarenal growth but not extending beyond Gerota’s fascia see below) 71 , whereas BAP1 mutations were associated with larger tumour sizes, higher Fuhrman nuclear grade (large nucleus with prominent nucleolus) and worse cancer-specific survival 77,78,80 . Interestingly, mutations in BAP1 and PBRM1 70 or KDM5C 20 seem to occur mutually exclusively in ccRCC, offering a molecular subclassification of ccRCC.…”
Section: Mechanisms/pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…As inactivation of VHL is the founding event of ccRCC, its mutation status has no effect on clinical outcome, whereas mutations involved in disease progression such as PBRM1 , SETD2 and BAP1 as well as KDM5C (which is also involved in chromatin modification) were shown to associate with aggressive clinical features 7779 . Small renal masses harbouring PBRM1 mutations were associated with stage III pathological features (that is, extrarenal growth but not extending beyond Gerota’s fascia see below) 71 , whereas BAP1 mutations were associated with larger tumour sizes, higher Fuhrman nuclear grade (large nucleus with prominent nucleolus) and worse cancer-specific survival 77,78,80 . Interestingly, mutations in BAP1 and PBRM1 70 or KDM5C 20 seem to occur mutually exclusively in ccRCC, offering a molecular subclassification of ccRCC.…”
Section: Mechanisms/pathophysiologymentioning
confidence: 99%
“…Interestingly, mutations in BAP1 and PBRM1 70 or KDM5C 20 seem to occur mutually exclusively in ccRCC, offering a molecular subclassification of ccRCC. Furthermore, mutations of KDM5C , which is located at Xp.11, were predominantly detected in male patients and correlated with long-term therapeutic benefit from sunitinib 20 ; and mutations of SETD2 were associated with reduced relapse-free survival 80 .…”
Section: Mechanisms/pathophysiologymentioning
confidence: 99%
“…Thus, TP53 mutation, PTEN mutation, and ICD might have prognostic value in chRCC. Likewise, BAP1, PBRM1, SETD2, and TP53 mutations in ccRCC (43)(44)(45), the CpG island methylator phenotype (CIMP) in pRCC (4), and the NF2 mutations in uRCC (8) are genomic features that have been shown to carry clinical significance in an RCC-subtype-specific manner. Thus far, all these genomic discoveries were made in retrospective studies utilizing archived tumor samples, which warrant further validation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the fact that PBRM1, SETD2, and BAP1 encode chromatin-and histone-regulating tumor suppressor proteins suggests epigenetic dysregulation as a convergent pathogenic theme in ccRCC [17]. As VHL loss is the truncal event during ccRCC development, its mutation status has no impact on clinical outcome [1], whereas PBRM1 [24], SETD2 [92], BAP1 [22,[92][93][94], KDM5C [95], TP53 [96], and TERT promoter [97] mutations are associated with more aggressive clinical features when all stages of ccRCC are considered, which is consistent with a notion that their loss occurs as a second, third or further downstream driver event [98]. Of note, mouse modeling demonstrated that PBRM1, a key component of the PBAF SWI/SNF chromatin remodeling complex, functions as a tumor suppressor by preventing self-perpetuating, feed-forward amplification of HIF oncogenic signals [51,99,100], and this may explain why its mutation in small renal masses is associated with tumor invasiveness [24].…”
Section: Clear Cell Rccmentioning
confidence: 99%